Metastatic castration-resistant prostate cancer in very elderly patients: challenges and solutions - Caffo O (Dove Medical Press, 2016)
Orazio Caffo, Francesca Maines, Mimma Rizzo, Stefania Kinspergher, Antonello Veccia Medical Oncology Department, Santa Chiara Hospital, Trento, Italy Abstract: The treatment of elderly patients with cancer is usually viewed by clinicians as a challenge, because of the age-related decline in normal organ function and the frequent concomitant administration of multiple drugs for comorbid conditions. Clinicians therefore tend not to prescribe antineoplastic agents (mainly in the case of chemotherapy) to elderly patients, with the fear of excess toxicity leading to an unfavorable cost:benefit ratio. The cutoff age defining a cancer patient as elderly is usually 70 years, but over the last 10 years clinicians have paid more attention to functional status, as evaluated by means of a comprehensive geriatric assessment and comorbidity burden, rather than chronological age. In the case of metastatic castration-resistant prostate cancer (mCRPC), depending on their age at the time of diagnosis of PC, many (if not most) of the patients are more than 70 years old, and a fair number are very elderly patients aged ≥80 years. The availability of various agents capable of significantly prolonging survival has dramatically changed the therapeutic landscape of mCRPC patients, but very elderly patients are usually underrepresented in pivotal trials. This narrative review considers the available data concerning elderly and very elderly mCRPC patients enrolled in pivotal trials and the information provided by reports of everyday clinical practice, in order to explore the challenges related to the clinical management of this special population. Keywords: prostate cancer, elderly, castration-resistant